Análisis de The End of Evangelion: Ikari Shinji y la negación del recorrido del héroe - Ayala Koo, Rodrigo Abelardo (2019)
This investigation will be centered on the analysis of the protagonist of the film The End of Evangelion, who will be studied through the concepts established by Joseph Campbell in his book The Hero of a Thousand Faces and through the use of Algirdas Greimas´s semiotic square and narrative programs.